General Rules on Invalidity of Contracts in Serbia - Dudás, Attila (Review of European and Comparative Law, 2022)
The effective Serbian Law on Obligations in the most part retained the general rules on invalidity of contracts from the former federal Law on Obligations from 1978. The Law explicitly differentiates two categories of invalid contracts: null and void contracts, on the one hand, and voidable contracts, on the other. Whereas the general legal consequences of both categories are principally the same, restitutio in integrum, null and void contracts have some other, more stringent legal consequences as well. The most important is the ban of restitution of performance of the party who acted in bad faith, which in cases when the contract grossly violates good morals may be supplemented by the forfeiture of the object of performance. The effective Serbian Law on Obligations, namely, still contains the rule retained from the former federal Law from 1978, according to which the court may order the party who acted in bad faith to transfer the object of his/her performance to the municipality of his/her residence or domicile. Voidable are considered contracts with flawed contractual intention, such as contracts concluded in mistake, deceit or under threat. In addition, voidable are contracts of minors older than 14 years concluded without the consent of their natural or legal guardian, or contracts of adults whose capacity is not completely excluded, but only partially reduced, concluded outside their capacity or without the consent of their legal guardian. Furthermore, since leasio is considered a case of mistake making the contractual intention flawed, the remedy is also the voidability of the contract. Under Serbian law, a contract is null and void, if it infringes public order, imperative rules or good morals, unless something else is prescribed by the law or the purpose of the infringed rule implies a different remedy. The illegality and immorality of a contract is scrutinised through its object (content) and cause. Aside these general rules, the Law on Obligations specifically qualifies usurious contracts as null. Yet, there are several means of „saving” a contract from the consequences of invalidity, primarily by performance, convalidation and partial invalidity. Non-existent contracts are clearly distinguished in the doctrine, but it is questionable whether the Law on Obligations envisages separate legal regime applicable to this category, distinct from the one applicable to null and void contracts. The law, namely, uses wording or implies in certain cases as if the contract had not been concluded at all. However, in the rules pertaining to legal consequences of invalidity refers only to null and void, and avoidable contracts. The doctrinal standpoints differ whether a separate legal regime applicable only to non-existent contracts could be implied from the general rules, regardless that no specific set of rules exists.